Stable Bipolar Patient Switched to Mania following Clinical Doses of Prednisone - Panwar, Vikram; Lassi, Krishan (Case Reports in Psychiatry, 2011)
We describe a stable bipolar female patient on medications that got switched into mania due to higher doses of prednisone prescribed for her severe sinusitis.